Mesa Redonda: La transferencia de inmueble en el Perú, los artículos 1135 y 2014 del Código Civil sobre la adquisición a través del non domino - Lama More, Héctor Enrique (2023)
What is the legal status of acquisitions by ‘nonowners’? Do they have constitutional protection? Does good faith relate to this? If so, would possessory verification be established? The purpose of this roundtable is to answer these and more questions so that the reader can contribute to the debate in the area of real estate.